Challenging the theoretical framework of the totalitarian syndrome - Bäcker, Roman; Rak, Joanna (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The article is of methodological nature and aims to evaluate the content validity of Carl Joachim Friedrich and Zbigniew K. Brzezinski’s totalitarian syndrome, that is, the extent to which this theoretical framework accurately represents the social phenomena to which it refers. It introduces the critical analysis of the individual concepts extracted from the totalitarian syndrome as the indicators of totalitarianism and the model as a whole as a research tool for measuring political regimes. The paper begins with the discussion on an alternative concept of totalitarianism formulated by Nicholas Timasheff to illustrate the context in which the authors of the theoretical categories of totalitarianism created them. Then, the article goes on to analyze the nature and major characteristics of Friedrich and Brzezinski’s totalitarian syndrome as well as these reviews of Totalitarian Dictatorship and Autocracy, which addressed the validity of the model. Social scientists have widely criticized Friedrich and Brzezinski’s totalitarian syndrome. The most serious objection concerns the non-specific essential features collected and combined to define totalitarianism. The taxonomic nature of the model has allowed researchers, who blindly adopted the framework, to classify discretionarily political regimes of numerous states as totalitarian. Friedrich and Brzezinski failed to advance any clear criteria for coding. They did not establish a line between meeting and not meeting the listed essential features. Furthermore, it is unknown what character the features enumerated under this syndrome have. This generates a question if the six “indicators” are essential, distinctive, significant, co-decisive, contours, features, factors, frames, pillars, or mechanisms. Although Friedrich and Brzezinski’s totalitarian syndrome fulfilled a prominent educational role mostly for US citizens by showing that there could be social worlds completely different from those in which one lives, the proposed understanding of totalitarianism is insignificant in defining such regimes. This theoretical framework inaccurately represents the social phenomena to which it refers. The paper finishes with the argument against applying the syndrome to scrutinize political regimes because of its considerably limited content validity.
Keywords: totalitarianism; totalitarian syndrome; Friedrich, Carl Joachim; Brzezinski, Zbigniew K.; non-democratic regime; theoretical model; content validity